Optimalisasi Peningkatan Kapasitas SDM dan Pengelolaan Keuangan Berbasis Akuntansi Sederhana bagi Pelaku UMKM di Kelurahan Harjosari II - Sari, Dian Purnama; Suginam, Suginam; Wardayani, Wardayani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This community service activity is carried out to increase the capacity of human resources (HR) and simple accounting-based financial management for MSME actors in Harjosari II. Many micro and small business actors do not have an adequate understanding of financial management and HR management, so they often face various obstacles in running and developing their businesses. Through this activity, the participants were given hands-on training on the importance of systematic financial records and strategies in managing human resources more effectively. The implementation method includes identifying the needs of MSME actors, preparing training materials, implementing training, and evaluating. From the activities that have been carried out, the results show that the majority of participants have increased understanding and awareness in implementing better management practices in finance and HR. Thus, this service is expected to be able to make a real contribution in strengthening the competitiveness and sustainability of MSME businesses in Harjosari II.